Endoscopic treatment of chronic pancreatitis in pediatric population: Long-term efficacy and safety - Kohoutova, D; Tringali, A; Papparella, G; Perri, V; Boškoski, I; Hamanaka, J; Costamagna, G (United European gastroenterology journal, 2019)
BACKGROUND: Chronic pancreatitis (CP) in children is an inreasingly recognized disease. OBJECTIVE: The purpose of study was to analyse the safety and long-term efficacy of endoscopic treatment in children with CP. METHODS: Records of 38 patients aged <18 years, referred to the Digestive Endoscopy Unit at Catholic University, Fondazione Policlinico "A. Gemelli" IRCCS between 1991 and 2017, were reviewed. Abdominal pain, analgesia and number of episodes of acute pancreatitis in the pre- and post- endoscopic retrograde cholangiopancreatography (ERCP) period were evaluated. Need for surgery was assessed. Therapeutic intervention data and complications were interrogated. RESULTS: In total 158 ERCPs were performed. Median post-ERCP follow-up was 7 years. The majority of patients had CP type IV (47%) and type Ib (37%) (Cremer's classification). Major papilla pancreatic sphincterotomy was performed in 47%, major and minor in 24% and minor in 29% of patients. Stones/plugs were removed in at least one ERCPs in 66% individuals. Eleven out of 38 patients had stricture of the pancreatic duct; these were dilated and stented in 5/11 and stented in 6/11. Five complications were recorded (3%). Severity and frequency of abdominal pain improved significantly; p < 0.001. Use of analgesia and number of episodes of acute pancreatitis decreased significantly; p < 0.001. One child required subsequent surgery. CONCLUSION: Endoscopic management of symptomatic CP in children is safe and effective.
Keywords: novorozenec; Infant, Newborn; Health Care Surveys; Infant; Humans; Pancreatitis, Chronic; Radiography; kojenec; ERCP; dítě; Precision Medicine; radiografie; endoskopie trávicího systému; Child; chronická pankreatitida; Female; věkové faktory; výsledek terapie; lidé; individualizovaná medicína; Cholangiopancreatography, Endoscopic Retrograde; předškolní dítě; Follow-Up Studies; ženské pohlaví; Chronic pancreatitis; stupeň závažnosti nemoci; cholangiopankreatografie endoskopická retrográdní; Male; Adolescent; Treatment Outcome; personalized medicine; Severity of Illness Index; průzkumy zdravotní péče; Age Factors; mužské pohlaví; efficacy and safety; Child, Preschool; Endoscopy, Digestive System; následné studie; mladiství; pediatric population